Uji Efektivitas Jenis Media Tanam dan Jenis Sumbu Sistem Wick Hidroponik Terhadap Produksi Tanaman Pakcoy (Brassica rapa L.) Varietas Nauli F1. - rommy andhika laksono (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
Utilization of local materials in the hydroponic system of axes such as planting media and types of axes can reduce production costs. The purpose of this study was to study and obtain a combination of growing media types and types of axes in the hydroponic wick system on the production of Pakcoy plants of Nauli F1 variety. This research was conducted in a community forest garden screen house on Jln. Wibisana, Sukaluyu Village, Teluk Jambe Timur District, West Karawang Regency from February to May 2016. The study used an experimental method using a single factor randomized block design (RBD) consisting of 9 treatments in 3 replications. (A. Cocopeat + Stove Wick); (B. Cocopeat + Flannelette); (C. Cocopeat + Cotton Cloth); (D. Husk Charcoal + Stove Wick); (E. Husk Charcoal + Flannelette); (F. Husk Charcoal + Cotton Cloth); (G. Rockwoll + Stove Wick; (H. Rockwoll + Flannelette); (I. Rockwoll + Cotton Cloth). The results of this study were significantly different effects of the combination of growing media types and different types of axes on the axis of the hydroponic system on plants, number of leaves, stem diameter, and fresh weight of pakcoy Nauli F1 varieties. The treatment medium for husk charcoal combined with the type of flannel axis was able to provide the highest fresh weight per plant of 36.93 g.